Application of activated charcoal and nanocarbon to callus induction and plant regeneration in aromatic rice (Oryza sativa L.). Issue 1 (1st January 2018) - Chutipaijit, Sutee; Sutjaritvorakul, Thanawat
Abstract: The investigations of nanotechnology with the application on agricultural products also have been few reported, especially the plant regeneration. The effects of activated charcoal and nanocarbon on the callus induction and plant regeneration of aromatic rice were studied. Activated charcoal was added into the callus induction and regeneration medium. The presence of activated charcoal in the callus induction medium (100–500 mg L −1 ), activated charcoal significantly reduced the percentage of the callus induction and biomass accumulation (fresh weight, dry weight and size). Whereas, the regeneration medium supplemented with 100 mg L −1 of activated charcoal showed the highest percentage of plant regeneration (61.90%) and the ratio of the number of seedlings to the number of regenerated calli (RSR; 3.06) that derived from the callus induction medium (without activated charcoal). Moreover, the induced calli derived from the callus induction medium supplemented with nanocarbon at 5 mg L −1 showed the highest percentage of callus induction (94.70%), the percentage of green spots (95.83%), the percentage of plant regeneration (60.42%) and the RSR (3.12) when transferred the calli into the regeneration medium (without nanocarbon). After that, nanocarbon was also added into the regeneration medium. The percentage of green spots (96.08%), the percentage of plant regeneration (62.75%) and the RSR (3.16) obtained from the regeneration medium supplemented with 20 mg L −1 of nanocarbon showed the highest values. This experiment showed that the optimum concentration of activated charcoal and nanocarbon had potential to enhance the callus induction and plant regeneration frequencies in tissue culture medium of aromatic rice.